PERBANDINGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MENGGUNAKAN MODEL PEMBELAJARAN SAVI DAN MODEL PEMBELAJARAN LANGSUNG SISWA KELAS VIII SMPN 2 KUALA TUNGKAL - Indri Jati Sugesti; Risma Simamora; Ayu Yarmayani (PHI: Jurnal Pendidikan Matematika, 2018)
Abstract: This research is an experimental research. Population in this research is all students of class VIII SMPN 2 Kuala Tungkal Academic Year 2017/2018. Sampling using simple random sampling while the research samples are taken class VIII A and VIII B. where two classes of samples are given different treatment. From the results of research conducted the average value for the experimental class is 80,75 with standard deviation 5,12 and the average control class is 68,12 with standard deviation4,92 and from the results of hypothesis test obtained tcount of 10,1 and ttable of 1,67 at the real level of 0,05. From the calculation it is seen that tcount greather than ttable then H1 accepted. Based on the final result, it can be concluded that the problem solving ability of mathematics students using SAVI (Somatic, Auditory, Visuallization, Intellectually) learning model is better than the Direct learning model in students of grade VIII SMPN 2 Kuala Tungkal.Keyword: Mathematical Problem Solving Ability, SAVI (Somatic, Auditory, Visualization, Intellectualy) learning model, Direct Learning Model.